2021
DOI: 10.1200/jco.2020.39.28_suppl.270
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life outcomes in adults with nonmuscle-invasive bladder cancer receiving a mitomycin-containing reverse thermal gel as a primary treatment (Optima II: Phase 2b, single-arm, open-label trial).

Abstract: 270 Background: The standard of care for low-grade non‐muscle‐invasive bladder cancer (LG NMIBC) is transurethral resection of the bladder tumor, which can worsen health‐related quality of life (HRQOL). The “OPTimized Instillation of Mitomycin for Bladder Cancer Treatment” (Optima II, clinicaltrials.gov: NCT03558503) is a Phase 2b, open label, single arm, multicenter trial evaluating a nonsurgical alternative as a primary treatment. Patients receive six weekly instillations of UGN-102, a mitomycin-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A clinical study has shown the feasibility of hydrogel therapy, with 44 bladder cancer patients achieving complete disease remission within 3 months. 53 However, further observation is necessary to determine long-term outcomes.…”
Section: Current Approaches and Advances For Intravesical Instillatio...mentioning
confidence: 99%
“…A clinical study has shown the feasibility of hydrogel therapy, with 44 bladder cancer patients achieving complete disease remission within 3 months. 53 However, further observation is necessary to determine long-term outcomes.…”
Section: Current Approaches and Advances For Intravesical Instillatio...mentioning
confidence: 99%